Two Case Reports of a Malignant Germ Cell Tumor of Ovary and a Granulosa Cell Tumor: Interest of Tumoral Immunochemistry in the Identification and Management - Bouquet de Jolinière, J.; Ben Ali, N.; Fadhlaoui, A.; Dubuisson, J. B.; Guillou, L.; Sutter, A.; Betticher, D.; Hoogewoud, H. M.; Feki, A. (Frontiers in Oncology, 2014)
Abstract Objective: In this article, we present two case reports. The first case was a malignant germ cell tumor of the right ovary in a 23 year old female and a case of a bilateral undifferentiated granulosa cell tumor in a 71 year old female. The aim of these reports is to illustrate the interest of the immuno-histochemical analysis to define the correct diagnosis, to better classify these ovarian tumours and improve their management. Methods: This study we report two cases. The first case concern a 23 years old woman (A) with a mixed germ cell tumour of the right ovary (dysgerminoma (75%), yolk sac tumour (20%), and a mature teratoma (5%), and the second case (B) a bilateral non differentiated and necrotic granulosa cell tumour of both ovaries concerning a 71 year old patient. The staging system used was according to both classifications, the one of International Federation of Gynaecology and Obstetrics (FIGO) 1987 for ovarian cancer, and the one of TNM code 2009. Results: The immunostaining establish the malignancy and the immunochemistry contribute to confirm effectively the right diagnosis (Table 2 and 3). Conclusion: An immuno-histochemical analysis is mandatory for the choice of chemotherapy to obtain the better response of the disease and improve the survival prognosis. The efficiency of the chemotherapy authorizes a conservative surgery including a unilateral salpingo-oophorectomy preserving fertility (A). Concerning the non-dysgerminoma tumour (B), and after a surgical staging and debulking, chemotherapy was recommended. The type of tumour and its histological feature conditioned the choice of treatment. The benefit of the immunohistological analysis in this case allowed the right adjuvant treatment. Key words: germ cell tumours, dysgerminoma, teratoma, yolk sac, ovarian cell tumour, and immunohistochemistry.